Evaluation of the Copan eSwab®, a liquid-based microbiology transport system, for the preservation of Neisseria gonorrhoeae at different temperatures. Issue 3 (25th August 2017) - Gumede, Lindy; Radebe, Frans; Nhlapo, Duduzile; Maseko, Venessa; Kufa-Chakezha, Tendesayi; Kularatne, Ranmini
Abstract : Aims and objectives: To evaluate the survival duration of Neisseria gonorrhoeae from male urethral discharge specimens collected using the Copan eSwab® liquid-based microbiology transport system, at both ambient and refrigerator temperatures. Methods: Three urethral swabs (one Dacron, two Copan eSwabs®) were collected from each male patient presenting with purulent urethral discharge to a community-based primary healthcare centre in Johannesburg. The Dacron swab was directly inoculated onto New York city agar medium, and the Copan eSwabs® transported and held at room and refrigerator temperature, for daily sub-culture onto New York city agar over a total period of seven days (168 h). The utility of Copan eSwabs® for the transport and survival of N. gonorrhoeae at different temperatures was determined by comparison to culture obtained by 'gold standard' direct plate inoculation. Results: N. gonorrhoeae isolation rates from Copan eSwabs® at fridge temperature and ambient temperature were as follows: 87.9% vs 79.3% at 48 h; 67.2% vs 60.3% at 72 h; 60.3% vs 22.4% at 96 h; and, 53.4% vs 3.4% at 120 h, respectively. The viability of subculture decreased significantly from eSwabs® maintained at room temperature from 96 h onwards of specimen collection. Conclusion: To ensure the preservation and an acceptable isolation rate of N. gonorrhoeae from urethral discharge specimens, Copan eSwabs® should be transported and maintained at refrigerator temperatures, and must reach the processing laboratory by at least 120 h (5 days) after collection.